Do AIS and innovation influence the relationship between business strategy and SME’s performance? - Zuhaila, Rofiqa; Halimatusyadiah, Halimatusyadiah (Manajemen dan Bisnis, 2024)
In the context of a dynamic and competitive business environment, SME actors must also possess a competitive advantage to succeed in the market. One strategy that can be pursued to achieve a competitive advantage is through the optimization of employee performance. This research aims to analyze the relationship between strategy and SME performance, encompassing the examination of innovation and accounting information systems as mediating variables. The study employs Structured Equation Modeling based on Partial Least Squares (SEM-PLS) analysis. The research involves 435 respondents who are SME actors with business units located in the province of Bengkulu. The findings indicate that strategy has a positive influence on SME performance. Furthermore, strategy also positively influences innovation and accounting information systems. In the context of indirect effects, both innovation and accounting information systems exhibit partial mediating effects in accommodating the relationship between strategy and SME performance. The results of this study emphasize that SME actors should be capable of crafting appropriate business strategies through various business innovations and improvements in accounting information systems, thereby enhancing SME performance.